Assessment of emotional intelligence in adults with down syndrome: Psychometric properties of the Emotional Quotient Inventory. - Sánchez-Teruel, David; Robles-Bello, María Auxiliadora; Camacho-Conde, José Antonio (PLOS, 2020)
The Emotional Quotient Inventory: Youth version-EQ-i:YV was developed by Bar-On & Parker in 2000 and later translated and adapted for the general Spanish adolescent population by Ferrandiz et al. in 2012. The Spanish scale presents similar psychometric properties to the original version (54 items and five subdimensions). The Emotional Quotient Inventory assesses a set of personal, emotional, and social skills that influence adaptation to and coping with environmental demands and pressures. These factors can influence an adolescent’s success later in life, health, and psychological well-being. Traditionally, research in Down syndrome (DS) has focused on identifying cognitive deficits, relatively little is known about emotional intelligence (EI) and there are no scales that measure EI in people with DS adults.
CC BY
Keywords: Emociones; Down, Síndrome de - Aspectos psicológicos; Psicometría